Penetrating cranial injury due to gunshot in a dog: a case report - S. Park; J. Park; J.M. Kim; J.H. Kim; J. Son; D. Chang; S.H. Choi; G. Kim (Veterinární Medicína, 2010)
A ten-month old, male Black and Tan Coonhound dog was referred with ocular bleeding due to gunshot injury. His mental state was normal. A computed tomography revealed that the bullet was planted in the left cranium. It was presumed that the trajectory of the bullet penetrated from the right medial angle of the eye to the orbit, and changed its track to caudo-dorsal by penetrating the cranium, ending up at the left cranium. The bullet was removed by lateral rostrotentorial craniectomy. No complications were observed during a one-year follow-up except the blindness in the right eye. This is a rare case of gunshot-induced traumatic brain injury featuring a bullet which went through the orbit into the cranium. The damaged frontal lobe seemed to show no neurological signs at the time of first examination in this case. In conclusion, a less aggressive surgical approach is recommended to remove bullets when they are accessible.